1998
DOI: 10.1021/bi9710683
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Fluorescein Derivative Eosin Y to the Mitochondrial ADP/ATP Carrier:  Characterization of the Adenine Nucleotide Binding Site

Abstract: As the SH-reactive fluorescein derivative eosin-5-maleimide (EMA) specifically labels Cys159 in the second loop facing the matrix space (loop M2) of the ADP/ATP carrier in bovine heart submitochondrial particles [Majima, E., Koike, H., Hong, Y.-M., Shinohara, Y., and Terada, H. (1993) J. Biol. Chem. 268, 22181-22187], we studied the interaction of non-SH-reactive eosin Y, an analog of EMA, with the carrier under various conditions to characterize its binding. Eosin Y was found to inhibit ADP transport by bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…2 56 was greatly reduced by BKA and this was taken to indicate that BKA binds close to these residues [29,30]. In support of this it was found that Eosin Y, an analogue of EMA that does not possess the thiol-reactive maleimide group, is a high affinity substrate analogue of the ANT whose binding is also inhibited by BKA but not CAT [30,36]. These data are consistent with there being a binding site for adenine nucleotides close to Cys 159 whose affinity for adenine nucleotides is conformationally dependent.…”
Section: Substrate Binding Sites and Their Sensitivity To Thiol Reagentsmentioning
confidence: 89%
See 1 more Smart Citation
“…2 56 was greatly reduced by BKA and this was taken to indicate that BKA binds close to these residues [29,30]. In support of this it was found that Eosin Y, an analogue of EMA that does not possess the thiol-reactive maleimide group, is a high affinity substrate analogue of the ANT whose binding is also inhibited by BKA but not CAT [30,36]. These data are consistent with there being a binding site for adenine nucleotides close to Cys 159 whose affinity for adenine nucleotides is conformationally dependent.…”
Section: Substrate Binding Sites and Their Sensitivity To Thiol Reagentsmentioning
confidence: 89%
“…We have proposed that these cysteines represent obvious candidates for the thiol groups that regulate both CyP-D binding and the inhibitory effects of ADP and membrane potential on the MPTP, and have provided extensive data to support this hypothesis [54,77,91]. Specific modification of Cys 159 within the adenine nucleotide binding site of the ANT with eosin maleimide not only inhibits adenine nucleotide binding and translocation by the ANT [29,36] but also almost totally abolishes the inhibition of the MPTP by ADP [54,77]. Furthermore, we have demonstrated that PAO chemically cross-links Cys 159 with Cys 256 whilst diamide causes a disulphide bond to form between these two cysteine residues through the mediation of oxidised glutathione [77].…”
Section: Thiol Groups On the Ant Play A Critical Role In Pore Openingmentioning
confidence: 97%
“…In essence the complimentarity between the transported solute and the intermediate (between m-and c-) states of the carrier provides the binding energy for the conformational change to occur. For example, purified ANT in CHAPS detergent adopts the m-state and is unable to bind atractylate unless ADP is added to catalyse the mstate-to-c-state conversion [45]. Thus ADP catalysis of PT pore flicker means that ANT must be in its native state between flickers ; if ANT were in a deformed state (but closed) between flickers, then the binding energy between ADP and ANT would not be available for the conformational change to the c-state to take place, and an open PT pore would not be produced.…”
Section: Adenine Nucleotide Translocase (Ant)mentioning
confidence: 99%
“…The conformational changes induced by nucleotide binding and stabilizing the nucleotide-Ancp complex are probably not mediated by movements around Ser-147. This residue is located in TMH3, which is directly linked to matrix loop m2, which was supposed to be the primary nucleotide binding site from the matrix space (43,44). However, as can be drawn from exchange measurements, Ser-147 participates in the conformational changes necessary to translocation although less importantly than Pro-43.…”
Section: Discussionmentioning
confidence: 99%